Latihan Invasi dapat Meningkatkan Kemampuan Dribbling, Passing dan Akurasi Shooting Futsal - Subakti, Subakti; Aminullah, Aminullah; Syobri, Nazalus; Hulfian, Lalu (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
Based on observations made, it was found that the futsal players on the team often failed to get past opponents and the ball in possession was easily snatched by opposing players, passes often went wrong and kicks on goal also had poor accuracy. This problem certainly needs to be overcome by providing forms of training to improve these abilities. One form of training that can be tried is invasion game training. Based on the background above, the researchers wanted to examine the effect of invasion training on the dribbling, passing and shooting accuracy abilities of the futsal extracurricular team players at SMAN 1 Terara. The aim of this research was to determine the effect of invasion training on the dribbling, passing and shooting accuracy abilities of extracurricular futsal team players at SMAN 1 Terara. The research method used was an experimental method with invasion training treatment. The research subjects were 28 players. The data collection technique is an action test and data analysis using paired sample t test analysis with the SPSS application. The results of the research show that there is an increase in the passing, dribbling and shooting abilities of the futsal extracurricular team players at SMAN 1 Terara because the value (sig.) < α (0.05) is (0.000 < 0.05), so H0 is rejected, H1 is accepte